Identification of breast cancer patients with pathologic complete response in the breast after neoadjuvant systemic treatment by an intelligent vacuum-assisted biopsy - Pfob, André; Sidey-Gibbons, Chris; Lee, Han-Byoel; Tasoulis, Marios Konstantinos; Kölbel, Vivian; Golatta, Michael; Rauch, Gaiane M.; Smith, Benjamin D.; Valero, Vicente; Han, Wonshik; MacNeill, Fiona; Weber, Walter Paul; et al. (European journal of cancer, 2021)
Neoadjuvant systemic treatment elicits a pathologic complete response (pCR) in about 35% of women with breast cancer. In such cases, breast surgery may be considered overtreatment. We evaluated multivariate algorithms using patient, tumor, and vacuum-assisted biopsy (VAB) variables to identify patients with breast pCR.
Available online 8 December 2020
Gesehen am 02.02.2021